2012
DOI: 10.1111/j.1349-7006.2012.02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2, Bcl‐6, and the International Prognostic Index are prognostic indicators in patients with diffuse large B‐cell lymphoma treated with rituximab‐containing chemotherapy

Abstract: This study aimed to clarify the clinicopathological prognostic parameters of de novo diffuse large B‐cell lymphoma (DLBCL) in the rituximab era. We examined the correlation of 22 clinicopathological parameters with progression‐free survival (PFS), overall survival (OS), and primary refractory disease in 285 DLBCL patients treated with rituximab‐containing chemotherapy. Complete response rate was 87%, overall response rate was 91%, 5‐year PFS rate was 72%, and 5‐year OS rate was 91%. By log–rank test, higher In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
7
12
3
2
Order By: Relevance
“…(30,31) However, this has recently become a controversial issue. (26,32) In the present study, neither GCB versus non-GCB nor the expression of CD10, Bcl-6, or MUM1 was a significant prognostic factor for cases of DLBCL transformed from FL.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…(30,31) However, this has recently become a controversial issue. (26,32) In the present study, neither GCB versus non-GCB nor the expression of CD10, Bcl-6, or MUM1 was a significant prognostic factor for cases of DLBCL transformed from FL.…”
Section: Discussioncontrasting
confidence: 72%
“…A high Ki-67 index is reported to be a poor prognostic parameter in de novo DLBCL (25) ; however, the issue is controversial. (26) In the present study, Ki-67 was a significant predictor of PFS and OS in univariate analyses, although this significance was not sustained in multivariate analysis. We found that a 100% proportion of DLBCL in DLBCL transformed from FL displayed a worse outcome than the other groups.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Bcl-6 protein is expressed in about 47–84% of DLBCLs. Bcl-6 rearrangement and Bcl-6 protein expression were reported to be associated with favorable clinical outcome [2528]. In the present study, Bcl-2 positivity and Bcl-6 negativity were found to be parameters predicting a significantly shorter PFS particularly (Figure 2).…”
Section: Discussionsupporting
confidence: 61%
“…Protein expression has been associated with poor outcome in most studies (21,3032). However, its survival impact appears to be modulated by rituximab (33,34).…”
Section: Resultsmentioning
confidence: 99%